Análise sobre a gestão do programa de aquisição de alimentos (PAA) e o desenvolvimento no meio rural no município de Itabuna - Bahia - Ramos, Diego Pita (2015)
Among the programs belonging to the bulge of the developed Social Policies recently in Brazil , is the Programa de Aquisiçao de Alimentos (PAA), which aims at the development of family farming through income generationin rural areas. The aim of this research is to analyze the management and implementation of the Food Acquisition Program - PAA in Itabuna -Bahia , and the socioeconomic development of rural areas of this county. Once Itabuna is the Brazilian city that captures the bulk of appeal with the MDS to run the PAA DoaçãoSimultânea, and is a reference at the national level as regards the management of this program . To understand the causes that contributed to Itabuna obtain this status , this research identified the institutions that assist in their management, and noted the fundamental contribution of the municipal legislature that in addition to monitoring the effective implementation of public expenditure allocated to PAA performs joints so that beneficiary associations obtain increasingly positive results; the contribution of CEPLAC and COOTEBA in providing assistance and rural technical assistance to groups supported. Currently, Itabuna benefits 13 groups of farmers, which deliver part of its production of food ( processed vegetables, legumes , roots and tubers , vegetables and eggs ) for this marketing channel , receiving social assistance actions of 36 allocated groups in the county. Thus , the PAA helps to overcome two problems: on the side of farmers , there is overcoming the bottleneck of marketing ; and by entities to support disadvantaged socioeconomically , have to ensure food and nutrition security in the city. Finally , it was observed that to ensure a development of the whole country , it is essential that the insertion of peri producers and the study of other marketing possibilities, since due to the program character , the PAA may have its closed actions according to State interests